2023
DOI: 10.1144/sp533-2022-80
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician Japan: geotectonic setting and palaeogeography

Abstract: Ordovician Japan formed a mature arc-trench system developed along the Paleo-Pacific (Panthalassa) margin of the Greater South China (GSC) continental block. GSC consists of South China, East China Sea, SW-NE Japan, and Khanka-Jiamusi-Bureya megablock in the Far East; thus in total twice as large as the South China components by itself (Yangtze and Cathaysia). The Ordovician crust of Proto-Japan comprised coeval arc-related rocks, such as granitoids, supra-subduction zone ophiolite, and fore-arc basin strata, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The new zircon ages confirmed that the East China Sea, SW-NE Japan, and Khanka block primarily, at least since the Cambrian, formed northeastern extensions of the South China block, in particular, the Cathaysian part on the Pacific side (Isozaki, 2019(Isozaki, , 2023Isozaki et al, 2017;Yamamoto et al, 2022). In this newly proposed framework named Greater South China (GSC; Isozaki et al, 2014), the KJB megablock in Far East Asia corresponds to a northernmost segment of GSC, although their present configuration and relative positions were drastically modified by later tectonics, which was culminated by the Miocene opening of the Japan Sea.…”
Section: West Of Gscmentioning
confidence: 57%
See 1 more Smart Citation
“…The new zircon ages confirmed that the East China Sea, SW-NE Japan, and Khanka block primarily, at least since the Cambrian, formed northeastern extensions of the South China block, in particular, the Cathaysian part on the Pacific side (Isozaki, 2019(Isozaki, , 2023Isozaki et al, 2017;Yamamoto et al, 2022). In this newly proposed framework named Greater South China (GSC; Isozaki et al, 2014), the KJB megablock in Far East Asia corresponds to a northernmost segment of GSC, although their present configuration and relative positions were drastically modified by later tectonics, which was culminated by the Miocene opening of the Japan Sea.…”
Section: West Of Gscmentioning
confidence: 57%
“…More research is needed to confirm the full spectrum and details of YTL, its geotectonic significance is potentially more than a simple divide between two neighboring granitoid provinces, because YTL likely represents a prominent boundary between two major orogens in Far East Asia, that is, EW‐trending CAOB and NS‐trending GSC‐Nipponides (Figures 1 and 7), as emphasized by Isozaki (2019, 2023). More details on the regional tectonics of relevant areas will be discussed elsewhere.…”
Section: Discussionmentioning
confidence: 99%